2014
DOI: 10.1371/journal.pone.0098294
|View full text |Cite
|
Sign up to set email alerts
|

β-Cryptoxanthin Alleviates Diet-Induced Nonalcoholic Steatohepatitis by Suppressing Inflammatory Gene Expression in Mice

Abstract: Recent nutritional epidemiological surveys showed that serum β-cryptoxanthin inversely associates with the risks for insulin resistance and liver dysfunction. Consumption of β-cryptoxanthin possibly prevents nonalcoholic steatohepatitis (NASH), which is suggested to be caused by insulin resistance and oxidative stress from nonalcoholic fatty liver disease. To evaluate the effect of β-cryptoxanthin on diet-induced NASH, we fed a high-cholesterol and high-fat diet (CL diet) with or without 0.003% β-cryptoxanthin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 39 publications
(47 reference statements)
4
56
0
Order By: Relevance
“…However, although previous studies demonstrated the beneficial effect of low dosage of astaxanthin and vitamin E (25-75 mg/kg) on oxidative stress [5,18,39,40], the variation of the dosage to balance the oxidative stress and exhibit the beneficial effect still unclear. Meta-analysis of the effect of the dosage on mortality by Abner et al found that a moderate dosage of vitamin E (cut-point of 400 IU/day or 330 mg/kg) did not affect the risk of all-cause mortality [41], whereas Miller et al found a significantly increased risk of mortality for doses above 400 IU [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although previous studies demonstrated the beneficial effect of low dosage of astaxanthin and vitamin E (25-75 mg/kg) on oxidative stress [5,18,39,40], the variation of the dosage to balance the oxidative stress and exhibit the beneficial effect still unclear. Meta-analysis of the effect of the dosage on mortality by Abner et al found that a moderate dosage of vitamin E (cut-point of 400 IU/day or 330 mg/kg) did not affect the risk of all-cause mortality [41], whereas Miller et al found a significantly increased risk of mortality for doses above 400 IU [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, although previous studies demonstrated the beneficial effect of low dosage of astaxanthin and vitamin E (25–75 mg/kg) on oxidative stress , the variation of the dosage to balance the oxidative stress and exhibit the beneficial effect still unclear. Meta‐analysis of the effect of the dosage on mortality by Abner et al.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 60 participants were included with obesity (BMI ≥ 30 kg m −2 ), of which 30 male and 30 female, aged 51 ± 12 (mean ± SD) years with a BMI of 39 [34][35][36][37][38][39][40][41][42][43][44]…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…We have previously reported that another xanthophyll carotenoid, β-cryptoxanthin, which is found particularly in Satsuma mandarin oranges ( Citrus unshiu Marc. ), attenuated fat accumulation, inflammation, and fibrosis in mice with CL diet-induced NASH [15]. Comprehensive gene expression analysis showed that β-cryptoxanthin effectively suppressed the expression of inflammatory genes but not the expression of the genes associated with steatosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…), attenuated fat accumulation, inflammation, and fibrosis in mice with CL diet-induced NASH [15]. Comprehensive gene expression analysis showed that β-cryptoxanthin effectively suppressed the expression of inflammatory genes but not the expression of the genes associated with steatosis [15]. The study suggested that β-cryptoxanthin suppressed inflammation and the resulting fibrosis primarily by suppressing the increase and activation of macrophages and other immune cells [15].…”
Section: Introductionmentioning
confidence: 99%